2023
DOI: 10.3390/insects14120921
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Rice Stemborer Assemblages: A Review of Species’ Distributions, Host Ranges, and Interspecific Interactions

Finbarr G. Horgan

Abstract: This review describes global rice stemborer assemblages based on published species distributions, apparent host preferences, and reported shifts in assemblage composition in response to environmental factors. At least 56 moth (Lepidoptera: Crambidae, Pyralidae, Noctuidae) and fly (Diptera: Diopsidae, Chloropidae) species have been associated with rice; however, only 21 species are of potential, large-scale economic importance with a further 2 species of localized concern; most of the remaining species’ associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 183 publications
0
4
0
Order By: Relevance
“…In the field, the A lines had profuse tillering and often attained a relatively large size compared to the fertile lines. Recent detailed studies of plant growth and stemborer occurrence in the Philippines has indicated that YSB—the predominant species occurring in our field plots—is associated with high tillering and relatively thick stems; and that much of the variability in stemborer damage to rice varieties can be explained by crop duration [ 40 , 60 ]. Rice varieties that are exposed for longer in the field tend to incur greater damage from stemborers, which is better regarded as crop ‘vulnerability’ and not ‘susceptibility’ [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the field, the A lines had profuse tillering and often attained a relatively large size compared to the fertile lines. Recent detailed studies of plant growth and stemborer occurrence in the Philippines has indicated that YSB—the predominant species occurring in our field plots—is associated with high tillering and relatively thick stems; and that much of the variability in stemborer damage to rice varieties can be explained by crop duration [ 40 , 60 ]. Rice varieties that are exposed for longer in the field tend to incur greater damage from stemborers, which is better regarded as crop ‘vulnerability’ and not ‘susceptibility’ [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be reduced by avoiding long-duration varieties, thereby reducing vulnerability [ 60 ]. However, even where varieties are selected to avoid specific stemborer-related susceptibilities, i.e., by reducing tillering to avoid YSB damage or reducing stem thickness to avoid SSB damage, other stemborers from the regional assemblage of species can become prevalent [ 40 ]. For this reason, calls have been made for greater attention to issues of rice tolerance to stemborers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations